2014
DOI: 10.5603/fm.2014.0002
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and radiometrical study of the human intervertebral foramina of the cervical spine

Abstract: (Folia Morphol 2014; 73, 1: 7-18)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ahmed et al reported the morphology of the human intervertebral foramina of the cervical spine. 21 There were no significant differences between the right and the left sides from C3-C4 to C6-C7 intervertebral levels. 21 Therefore, patients with wide WIF at the C4-C5 and C5-C6 intervertebral levels on the normal side originally tend to have wide WIF at the C4-C5 and C5-C6 intervertebral levels on the affected side.…”
Section: Factors Associated With Group 1 Statusmentioning
confidence: 75%
See 1 more Smart Citation
“…Ahmed et al reported the morphology of the human intervertebral foramina of the cervical spine. 21 There were no significant differences between the right and the left sides from C3-C4 to C6-C7 intervertebral levels. 21 Therefore, patients with wide WIF at the C4-C5 and C5-C6 intervertebral levels on the normal side originally tend to have wide WIF at the C4-C5 and C5-C6 intervertebral levels on the affected side.…”
Section: Factors Associated With Group 1 Statusmentioning
confidence: 75%
“…21 There were no significant differences between the right and the left sides from C3-C4 to C6-C7 intervertebral levels. 21 Therefore, patients with wide WIF at the C4-C5 and C5-C6 intervertebral levels on the normal side originally tend to have wide WIF at the C4-C5 and C5-C6 intervertebral levels on the affected side. We considered that WIF at the C4-C5 and C5-C6 intervertebral levels on the affected side may have become narrower due to degenerative changes.…”
Section: Factors Associated With Group 1 Statusmentioning
confidence: 75%
“…17 Other studies have focused on the use of oblique radiographs to best capture the IVF; [18][19][20] however, these studied the cervical foramina, and there are minimal studies involving oblique radiographs of the lumbar foramina. Cervical and lumbar anatomy, particularly at the IVF, also have significant differences in the position of nerve roots relative to the disc plane and the percentage of neural tissue occupying the foraminal space, 21,22 which may influence the impact of vertebral osteophytes on nerve impingement. In addition, patients in our cohort rarely had oblique lumbar radiographs available, rendering these measurement approaches obsolete.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalances between apoptosis and regeneration cause the regression of the intervertebral disc (1). Apoptosis is as essential as the function of proteoglycan synthesis in determining the possible degeneration of intervertebral discs.…”
Section: Introductionmentioning
confidence: 99%